(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the species’ behavior through the importance value index, we verified the changes that occurred in the diversity of commercial trees over time. Species variety was determined by the Importance Value Index (IVI) and then classified into groups of use. Sapotaceae was the most abundant family in the entire study, with the largest volume and basal area. Pouteria spp., Goupia glabra and Manilkara huberi can be selected for a new harvest due to the recovery in growth rate. Currently, 16 commercial species can be used for a second forest harvest plus 52 new species. There must be studies of new species to compose the forest exploitation taking into account the number of remaining individuals, their distribution in the area and the dominance of this species in relation to other individuals.